SEM evaluation of smear layer removal by two different single file system along with various irrigating solutions - An in vitro study - Kavitha Ramachandran; Meenakshi Sundaram Rajasekaran; Anil Kumar Ramachandran; Gopal Shankar Narayan; Sokkalingam Mothilal Venkatesan (Endodontology)
Aim: The objective of this study was to compare the efficacy of smear layer removal from root canal using two different instrumentation systems, HyFlex electrical discharge machining (EDM) and WaveOne Gold, and to evaluate the smear layer removal ability of three different irrigants, Qmix, sodium hypochlorite (NaOCl), and ethylene diamine tetraacetic acid (EDTA). Methods: Sixty single-rooted human mandibular premolars without caries or developmental defects were divided into two groups: Group A (HyFlex EDM) along with NaOCl (A1), EDTA (A2), and Qmix (A3), Group B (WaveOne Gold) along with NaOCl (B1), EDTA (B2), and Qmix (B3) were used. The root canals were prepared according to the assigned instrumentation system and irrigants. The prepared teeth were then split longitudinally, and scanning electron microscopy was employed to assess and photograph the samples. Results: The results indicated that the WaveOne Gold-Qmix subgroup (B3) showed significantly better smear layer removal scores when compared to other subgroups. Furthermore, there was a significant difference in smear layer removal between the coronal and middle thirds of the root canal, while there was no significant difference observed in the apical third. Conclusion: WaveOne Gold instrumentation system exhibited superior smear layer removal ability compared to the HyFlex EDM. Moreover, the Qmix irrigant showed better smear layer removal efficacy than NaOCl and EDTA. The findings also emphasized the importance of considering the location within the root canal, as increased smear layer removal was observed in the coronal and middle thirds compared to the apical third.